Comic-film-music of “Pendekar Cyborg”: a case study of transmedia storytelling in Indonesian contemporary independent comics - Bajraghosa, Terra; Irawanto, Budi; Ajidarma, Seno Gumira (International Journal of Visual and Performing Arts, 2025)
This study explores independently published comics in Indonesia after 2010, which show differences from independent comics in the late 1990s and early 2000s. Contemporary independent comics distinguish themselves by positioning readers as patrons and the application of transmedia storytelling across platforms, especially related to film and music, and not for industrial purposes. The research questions presented are: what are transmedia storytelling practices in contemporary independent comics in Indonesia, and how is the context of creative freedom and control that underlies the production of printed comics presented through cross-media platforms? Using qualitative methodology, this study applies descriptive discourse analysis based on the visual culture framework, following Gillian Rose's methodological approach. The descriptive analysis focuses on the case study of transmedia storytelling "Pendekar Cyborg", an independently published comic series, which intersects with other media such as motion comics, animated music videos, film, and music. The findings show that contemporary Indonesian independent comics engage in canonical transmedia storytelling, in dimensions of spreadability, continuity, and multiplicity, while still reflecting the socio-political context. The work “Pendekar Cyborg” affirms creative freedom within an independent artistic community and expands narrative experiences through innovative, creator-driven transmedia strategies with community support. This research contributes to understanding how independent visual storytelling in Indonesia embraces transmedia formats to negotiate cultural meaning and audience engagement.